Hubungan Pemberian ASI dengan Perkembangan Anak Usia 24-36 Bulan Melalui Skrining DDST - Fikri Lutfiatus Sa’adah; Jenie Palupi; Syiska Atik Maryanti (Puslitbang Sinergis Asa Professional, 2022)
Based on Riskesdas (2018) coverage of exclusive breastfeeding in Indonesia does not meet the SPM target set by the government which is 80%, coverage in East Java is 40%, in Jember Regency the lowest coverage in Andongsari Health Center is 24.51%, this will affect the scope of child development in the region. East Java Province is targeting 2020 early detection coverage growth of 95% while the current coverage is 53.44%. This study aims to determine the relationship of breastfeeding with the development of children aged 24-36 months through DDST screening in Pontang Village, the working area of Andongsari Health Center, Jember Regency. This type of research is analytic correlation with cross-sectional approach, the population of all mothers who have children aged 24-36 months, obtained a sample of 69 respondents in 6 posyandu with simple random sampling technique. The research instrument was in the form of a questionnaire to assess the history of breastfeeding and a form of DDST to assess progress. Data analysis using chi-square test with SPSS program. The results obtained 51% with a history of non-exclusive breastfeeding, and 49% exclusive breastfeeding. The results of the development assessment were 81% normal, and 19% were suspected. The analysis results obtained p value 0, 241> α (0,05) ie there is no significant relationship between breastfeeding and the development of children aged 24-36 months. Even though the child is given exclusive breastfeeding, child development is not only influenced by breastfeeding, but other internal and external factors can influence.